Estimations on risk and bureaucracy: Sensitivity method - Challoumis Constantinos; Savić Marko; Constantinou Alexios (Ekonomski Pogledi)
In this paper, risk and bureaucracy are discussed in the tax system. It is indicated that bureaucracy decreases tax revenue, and the same result is shown regarding risk. The methodology applied will be based on S.M. (Sensitivity Method), where, through graphical analysis, the comparison between the risk and the bureaucracy will take place. The mathematical background and the theory of the money cycle specify the behavior of these variables. This work aims to show the interaction of these variables. The scope of this paper is to confirm the behavior of the theory Cycle of Money, considering these variables.